2011
DOI: 10.1172/jci57762
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic stimulation of type I interferons during influenza virus coinfection promotes Streptococcus pneumoniae colonization in mice

Abstract: Pneumococcal infection of the respiratory tract is often secondary to recent influenza virus infection and accounts for much of the morbidity and mortality during seasonal and pandemic influenza. Here, we show that coinfection of the upper respiratory tract of mice with influenza virus and pneumococcus leads to synergistic stimulation of type I IFNs and that this impairs the recruitment of macrophages, which are required for pneumococcal clearance, due to decreased production of the chemokine CCL2. Type I IFN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
276
3
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(298 citation statements)
references
References 45 publications
15
276
3
4
Order By: Relevance
“…Similar findings were reported when chickens were infected with H9N2 in combination with Staphylococcus aureus or Avobacterium paragallinarum or Ornithobacterium rhinotracheal (Kishida et al 2004, Pan et al 2012. Co-infection studies of influenza virus and Streptococcus pneumoniae in mice promoted bacterial colonization in the presence of viral infection (Nakamura et al 2011). We assume that MG induces considerable immune-suppression leading to enhanced replication of NDV yielding high mortality and morbidity rates under field conditions.…”
Section: Serological Examinationsupporting
confidence: 83%
“…Similar findings were reported when chickens were infected with H9N2 in combination with Staphylococcus aureus or Avobacterium paragallinarum or Ornithobacterium rhinotracheal (Kishida et al 2004, Pan et al 2012. Co-infection studies of influenza virus and Streptococcus pneumoniae in mice promoted bacterial colonization in the presence of viral infection (Nakamura et al 2011). We assume that MG induces considerable immune-suppression leading to enhanced replication of NDV yielding high mortality and morbidity rates under field conditions.…”
Section: Serological Examinationsupporting
confidence: 83%
“…We detected prolonged and systemically increased levels of IL-6, which alone or together with type I IFNs induced by PR8 and S. pneumoniae (63,64) could account for the exaggerated ASC response in the medLN of PR8ϩSp-coinfected mice at day 10 p.i. This model is consistent with studies that demonstrated that IL-6, IFN-␥, and type I IFNs can enhance Ab responses (30,(65)(66)(67).…”
Section: Discussionmentioning
confidence: 81%
“…While crucial for viral clearance, the release of (particularly type I) IFNs appears to blunt several antibacterial responses by suppressing the expression of AMPs, macrophage and/or neutrophil recruitment and TH17 responses (Kudva et al, 2011;Lee et al, 2015;Nakamura et al, 2011;Shahangian et al, 2009). In contrast, exogenous IFN-b was found to inhibit bacterial transmigration and thus to protect mice from developing bacteraemia after instillation of S. pneumoniae, suggesting an ambiguous role for type I IFNs during (secondary) bacterial infection (LeMessurier et al, 2013).…”
Section: Cytokines and Other Secreted Mediatorsmentioning
confidence: 99%